Pertanggungjawaban Pidana Terhadap Orang Yang Membantu Melakukan Tindak Pidana Penipuan (Studi Putusan Pengadilan Negeri Medan No. 541/Pid.B/2015/PN.Mdn. jo. Putusan Mahkamah Agung RI No. 216K/PID/2016) - Nanin Aprilia Fitriani; Sunarmi Sunarmi; Madiasa Ablisar; Muhammad Ekaputra (USU LAW JOURNAL, 2019)
Abstract : Non-Performing Loans are pure civil events between creditors and debtors, with assumptions as long as all the valid conditions of the Credit Agreement (PK) can be fulfilled by the parties including their collateral. With this condition, bad credit due to the inability of the debtor to pay off, the collateral can be auctioned through execution in court, which results in the auction to pay the loss of the bank or creditor. Bad credit can turn into a criminal event because there is a violation of law, both before and after the credit agreement is signed. As is known, there are 4 (four) conditions that must be fulfilled for the validity of a Credit Agreement, namely: The ability of legal subjects, the quality of legal subjects or not having legal standing to submit and sign a Credit Agreement; There is agreement between Creditors and Debtors, facta sunservanda, binding agreement as a law for those who make it; There is an object in this case borrowed money; and Causal, this Credit Agreement is made not to violate even the unwritten laws and regulations. In the example case raised in this study related to the provision of credit facilities by PT. Bank Sumut to customers who use third party collateral. The purpose of the provision of these credit facilities is to finance the Project "Concrete Jember Construction Work in Sako Estate, Central Kalimantan" which has been obtained by PT. Manunggal Adijaya Utama, as stated in the Contract (Work Order (SPK)) No. 107 / LOA-SKOE / VIII / 2009, August 11, 2009, with a Contract Value of Rp.1,160,000,000.- (One Billion One Hundred Sixty Million Rupiah). However, after the credit disbursement, it turned out that the funded project suffered a natural disaster, in other words the project became a loss.   Keywords : criminal liability, criminal acts; and fraudulent